Foreign experience in the use of а digital tools in regions and cities in the pandemic context - N. S. Sergienko (Вестник университета)
The COVID-19 crisis has accelerated separate megatrends and transformations not only in the social sphere, but also in the digital one in the public administration system. Information exchange, electronic participation and two-way communication using digital platforms allowed public authorities and business structures to respond promptly to the crisis in the short term. The urgency of the issues to be solved determined the adoption of measures not only in the short term prospect, but also indicated the need to develop them for the medium and long term period. The aim of the study was to analyse and systematise the set of measures taken by public authorities in different countries, in the mobilisation and crisis management of COVID-19. An important aspect of the study seems to be the identification of directions for digitalisation and further state and municipal digital services modernisation. The analysis of the measures taken by public authorities in different countries has highlighted that the policy of accelerating the digitalization of public administration and the public services provision in regions, cities and rural areas had helped to solve the social and economic problems. The regional and local measures versatility in different countries on digitalization in the medium term prospect makes it possible to form common approaches for using this experience in order to further modernize state and municipal digital services.